and, the, to, of Arbitration and Alternative Dispute Resolution Outside the Court According to Law Number 14 of 2001 On Patent - Seno Wibowo Gumbira; Adi Sulistiyono; Soehartono Soehartono (Hang Tuah Law Journal, 2020)
This article examines the services of arbitration institutions and Alternative Dispute Resolution in resolving disputes concerning deficiencies in the dispute resolution process held in courts. Due to the lack of the litigation process, concerns on legal certainty or sense of justice may not be achieved are raised among the disputing parties, thus dispute resolution held outside the court emerges, in particular within the Patent Law prescribes in Article 124, refers to Arbitration and Alternative Dispute Resolution. Arbitration denotes a different nature with ADR due to its adjudicative nature which tends to generate win-lose decisions, while ADR has consensus or cooperative nature which prefers to dispose win-win solution decisions. Other forms of ADR are Consultation, Mini-trial, Summary Jury Trial, settlement with organizations, etc. Arbitration and ADR enable a renewal in the settlement of Patent disputes as expected by the public, the deficiency of ADR prescribes in Article 124 of the Patent Law has explicitly stipulated ADR, however the elucidation mentions that ADR comprises negotiation, mediation, conciliation, and other forms in conformity with the laws and regulations.